Introjective identification: the analytic work of evocation*. Issue 4 (December 2016) - Eekhoff, Judy
Abstract This paper focuses on a particular counter-transference process—introjective identification and the evocation it enables. Introjective identification enables evocation because it engages the analyst's radical openness to the experience of the patient at the most primordial level. The accumulated wisdom of Ferenczi and those who followed him is used to discuss the role of introjective identification in the treatment of patients with non-neurotic structures.